Insolvensi dan Likuiditas pada Kinerja Keuangan Bank Syariah yang Terdaftar di Bursa Efek Indonesia - Rara Riezka Hidayati; Aminar Sutra Dewi (Lembaga Yasin AlSys, 2026)
Studies on the financial performance of Islamic banks continue to develop, but discussions that specifically examine the effect of insolvency and liquidity on the financial performance of Islamic banks in Indonesia still need to be strengthened. This study aims to analyze the effect of insolvency and liquidity on the financial performance of Islamic banks registered with the Financial Services Authority for the 2019–2023 period. This study employed a quantitative approach with an associative design. The research population included 14 Islamic banks, while the sample was determined through the purposive sampling technique. The research data consisted of secondary data obtained from the annual financial reports of Islamic banks through the official website of the Financial Services Authority and the official websites of each bank. Data were collected through documentation techniques and then analyzed using descriptive statistics and panel data regression with the assistance of EViews. The results show that insolvency and liquidity have a significant effect on the financial performance of Islamic banks. These findings provide an empirical contribution to enriching the study of banking financial management, particularly regarding the role of internal financial soundness in supporting the performance of Islamic banks. The conclusion of the study emphasizes the importance of properly managing insolvency and liquidity. The practical implication is that bank management needs to strengthen risk and liquidity management strategies to maintain the stability and profitability of Islamic banks.